L'Università degli Studi di Firenze fra istituzioni e cultura nel decennale della scomparsa di Giovanni Spadolini - Ceccuti, Cosimo (Firenze University Press, 2005)
This book contains the proceedings of the conference held on 11 and 12 October 2004 in the Aula Magna of the University of Florence, in collaboration with the Fondazione Spadolini. The aim of the conference was to delineate the profiles of a series of emblematic figures, representative of the presence and activities of illustrious teachers from the University of Florence in local and national institutions and in civil society. The proceedings are conceived to act as permanent evidence of the close links between the University and the Institutions and of the major impact of the work of so many lecturers from the University of Florence in the recent history of Italian institutions.